Activated PI3Kδ syndrome in inborn errors of immunity: diagnostic strategies and clinical challenges - Bozkurt, Selcen; Ozturk, Necmiye; Altunbas, Melek Yorgun; Can, Salim; Amirov, Razin; Mahmudov, Ramin; Colak, Burkay Cagan; Karabiber, Esra; Baronio, Manuela; Lougaris, Vassilios; Tessarin, Giulio; Bilgic-Eltan, Sevgi; et al. (Frontiers in Immunology, 2026)
IntroductionThis study aims to present in a large real-world cohort a diagnostic algorithm developed to facilitate the early recognition of Activated Phosphoinositide 3-Kinase Delta Syndrome (APDS), a rare disease with targeted treatment options, and to provide clinicians with a practical roadmap for navigating diagnostic challenges.MethodsThe study was conducted as a retroactive cross-sectional observational study. We reviewed the medical records of 6,458 pediatric and adult patients who were referred to our clinic between 2018 and 2025. A medical algorithm was generated based on major clinical and laboratory features of APDS. Next-generation sequencing analyses were performed on patients who were appropriate for further evaluation. Variant analysis using in silico predictors and S6 phosphorylation analysis in patients carrying previously undescribed variants were conducted accordingly.ResultsIn this cohort of 6,458 patients, the diagnostic algorithm identified 1,138 who met at least one major clinical or laboratory criterion. After excluding 7 with a prior APDS diagnosis and 573 with other inborn errors of immunity, genetic analysis was performed in 20 consenting patients under clinical follow-up (11 [55%] female, 9 [45%] male; median age 15 years; IQR 7.5–24). APDS type 2 was confirmed in 1 patient; five others harbored novel variants of uncertain significance.ConclusionDelayed diagnosis and treatment of APDS may result in life-threatening complications and irreversible end-organ damage. Given its heterogeneous, overlapping phenotype, timely referral for genetic testing is essential.